Localized Corrosion Behaviour of Cu-lean AA 7003 Extrusions - krishnan, charanya (My University, 2011)
A study was undertaken to achieve a better understanding of the key microstructure-performance relationships involved with the intergranular corrosion and exfoliation corrosion of Cu-lean AA7003 alloy extrusions, as a function of the heat-treated condition. The heat treatments of interest in this study include the naturally-aged T4 condition, representing the as-extruded condition, an artificially-aged T6 condition, representing a post-weld stress-relief condition, and an artificially-aged automotive paint-bake cycle condition. The influence of heat treatment on the resultant microstructure is characterized using light optical microscopy, coupled with image analysis, and electron (scanning & transmission) microscopy, coupled with energy dispersive spectroscopy. The influence of heat treatment on the corrosion behaviour is characterized using anodic polarization measurements and ASTM standardized testing to evaluate the susceptibility resistance to intergranular corrosion (ASTM G110) and exfoliation corrosion (ASTM G34).
The cross-sectional (LT-ST & L-ST) microstructures of all three heat treatments consist of a fibrous, non-recrystallized grain structure in the interior, and a coarse recrystallized grain structure at the exterior surface. Both grain structures are slightly elongated along L-direction. The grain size distribution and grain aspect ratio distribution is weakly dependant on the heat treatment applied, and on the orientation plane. Among the two artificial aging, the T6 (post-weld stress-relief) condition has the higher micro-hardness (yield strength), as it has higher density (volume fraction) of the strengthening MgZn2-type precipitates (η, η′ and their GP zones) within the Al matrix grains.
Anodic polarization measurements show a more negative corrosion potential (Ecorr) for the two artificially aging heat-treated conditions. The shift is believed to be due to the micro-galvanic cell activity established between the more noble Al matrix grains and the more active strengthening MgZn2-type precipitates within the Al matrix grains, which have a significantly increased surface area (volume fraction) in the artificially-aged condition. A similar, single breakdown potential (Eb) corresponding to a pitting potential (Epit) is observed, regardless of the heat-treated condition. The similar potential is believed to be due to localized breakdown of the passive film at the periphery of coarse second phase intermetallic particles (Al3Fe), which remain unaffected by artificial aging.
Of the three heat-treated conditions studied, the T6 condition exhibits the lowest susceptibility to both intergranular corrosion and exfoliation corrosion. The lower susceptibility is believed to be due to the lack of any Cu enrichment in across the grain boundary region (either in the solute depted zone or in the generic Mg(Zn,CuAl)2 grain boundary precipitates). This lack of enrichment is believed to produce a smaller micro-galvanic cell activity across the grain boundary region, as compared to that produced when Cu is enriched across the grain boundary region, particularly in the Solute depted zone (SDZ).
Keywords: aluminum alloy; exfoliation corrosion; microstructure; Engineering; Engineering